2021
DOI: 10.1111/jfpp.15863
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and 1‐methylcyclopropene treatments on delay senescence of apricots during postharvest cold storage by enhancing antioxidant system activity

Abstract: The effect of melatonin (MT) dipping and 1-methylcyclopropene (1-MCP) fumigation either individually or combined, on reducing delaying fruit senescence in apricot fruit was investigated. The results showed that the individual and combined MT and 1-MCP treatments maintained the quality of apricot fruits after harvest and reduced fruit softening, rot, and weight loss. This was mainly attributed to the high levels of ascorbic acid content, total phenol content, and total flavonoid content, as well as the upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, the effects of the three treatments on each kind of flavonoid and the same treatment on different flavonoids were not consistent. It is reported that the application of benzoic acid [ 14 ], chlorine dioxide [ 38 ] and 1-MCP [ 52 ] could increase the total flavonoids contents in some crops. After 20 d of storage, the concentration of hesperetin in the chlorine dioxide treatment was higher than that in the control, while the concentration of hesperetin in benzoic acid and 1-MCP treatments was lower than that in the control, and the concentration of hesperetin in the benzoic acid treatment was the lowest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of the three treatments on each kind of flavonoid and the same treatment on different flavonoids were not consistent. It is reported that the application of benzoic acid [ 14 ], chlorine dioxide [ 38 ] and 1-MCP [ 52 ] could increase the total flavonoids contents in some crops. After 20 d of storage, the concentration of hesperetin in the chlorine dioxide treatment was higher than that in the control, while the concentration of hesperetin in benzoic acid and 1-MCP treatments was lower than that in the control, and the concentration of hesperetin in the benzoic acid treatment was the lowest.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was in agreement with other reports showing that treatment with chlorine dioxide enhanced the postharvest synthesis of flavonoids and nonflavonoids, an effect opposite to that of 1-MCP [ 38 ]. Chlorine dioxide might delay the degradation of flavonoids by increasing the activity of the PAL and promoting the metabolism of phenylpropane, while 1-MCP might present the opposite [ 38 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, sweet potato decays easily during storage due to its high water content ( Sugri et al, 2017 ). Even at appropriate storage temperatures, crops still undergo deteriorative changes resulting from the activity of internal factors, such as ROS, a key contributor to postharvest senescence ( Wang et al, 2019 ; Guo et al, 2021 ). ROS can be produced in plants during many metabolic reactions, but particularly in chloroplasts and mitochondria during senescence.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, dipping in calcium chloride and then applying 1-MCP was a successful strategy to improve fresh-cut strawberries and watermelon quality during storage [ 26 , 27 ]. Other natural origin compounds as carvacrol [ 28 ] or elicitors as methyl salicylate [ 29 ] and melatonin [ 30 ] have increased shelf-life delaying ripening when these treatments were applied in combination with 1-MCP in red pitaya, tomato fruit, and apricot respectively. However, none of these studies have evaluated the chilling tolerance provided by a combined effect of the previous mentioned strategies.…”
Section: Introductionmentioning
confidence: 99%